#### Answer

$120 -35i$

#### Work Step by Step

$-5i(4 - 3i)^2= -5i(16 -12i - 12i + 9i^2) = -5i(16 - 24i + 9(-1)) $
$=-5i(7 - 24i) = -35i + 120i^2 = -35i +120(-1) =- 120 -35i$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$120 -35i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.